Existence of periodic solutions of impulsive differential systems. (1991) - Erbe, L. H.; Liu, Xinzhi
Abstract : In this paper, the existence of periodic solutions of impulsive differential systems is considered. Since the solutions of such a system are peicewise continuous, it is necessary to introduce piecewise continuous Lyapunov functions. By means of such functions, together with the comparison principle, some sufficient conditions for the existence of periodic solutions of impulsive differential systems are established.